Literature Review: Comparison of the Quality of Delivery Services at Independent Midwife Practices and Public Health Center - Solichati, Solichati; Agushybana, Farid (Faculty of Public Health, Universitas Diponegoro, Semarang, Indonesia, 2023)
Introduction: The role of quality service is important for health facilities to maintain their existence in the community, including Public Health Centers and Independent Midwife Practices that provide delivery services for pregnant women. Delivery services at health care facilities are one of the factors leading to the reduction of the Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR). This review was conducted to determine a comparative picture of the quality of delivery services at Independent Midwife Practices and Public Health Center.Methods: The study was conducted using a literature review approach of national journal articles retrieved from the Google Scholar database. The keywords used were quality of delivery services, quality of delivery services, patient satisfaction, Independent Midwife Practices, and Public Health Center. With a publishing range of no more than the last 5 years or from 2018-2023.Results: Five journals were eligible to be analyzed in relation to the quality of delivery services. The study showed that the quality of health services at the Independent Midwife Practices and Public Health Center is influenced by the factors of reliability, responsiveness, assurance, empathy, and tangibles. Both the Independent Midwife Practice and the Public Health Center have good quality of service in childbirth.Conclusion: It is important to maintain the quality of childbirth services both at Independent Midwife Practices and at Public Health Center.